Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jfpp.16165
|View full text |Cite
|
Sign up to set email alerts
|

Potential of low‐dose aqueous ozone treatment and packaging to extend quality and shelf‐life of green pea pods under cold storage

Abstract: Green pea (Pisum Sativum L.), a highly cultivated and popular vegetable in India, belongs to the leguminosae family. It is a rich source of vitamin B 9 , vitamin C, and vitamin K, as well as protein, carbohydrates, and minerals (Kaur et al., 2020). Green pea is a non-climacteric, highly respiring, and perishable product with limited shelf life of 4-5 days under ambient conditions (12 ± 5°C and 72% ± 5% RH).Current marketing practices involve on-farm packaging of green pea pods in jute/leno bags and transport t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…The time to saturate ozone gas at a known concentration was reported as 15-20 min. The treatment period of 60 min was recorded once the desired concentration of gas was reached (Kaur et al, 2021). The untreated FMF was considered as control.…”
Section: Raw Materials and Ozonation Treatmentmentioning
confidence: 99%
“…The time to saturate ozone gas at a known concentration was reported as 15-20 min. The treatment period of 60 min was recorded once the desired concentration of gas was reached (Kaur et al, 2021). The untreated FMF was considered as control.…”
Section: Raw Materials and Ozonation Treatmentmentioning
confidence: 99%
“…Ascorbic acid is a common constituent of most fruits and vegetables and is usually destroyed during processing through the combined action of heat, oxygen and light 47 . It was observed that the maximum value of ascorbic acid was observed in the sample dried using ADSD (24.29 ± 1.81 mg/100 gdw) and the minimum value was observed in the OSD (21.37 ± 0.03 mg/100 gdw) sample as shown in Table 3.…”
Section: Resultsmentioning
confidence: 95%